Planned organizational change to transform care to workers exposed to biological material - Luana Cássia Miranda Ribeiro; Denize Bouttelet Munari; Adenicia Custódia Silva e Souza; Katiane Martins Mendonça; Lucieli Dias Pedreschi Chaves; Zilah Cândida Pereira das Neves (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to describe the evaluation of the service offered in cases of occupational accidents involving exposure to biological material, from the perspective of the exposed workers, before and after an intervention to obtain planned organizational change. Methods: descriptive study with a qualitative approach, carried out with workers exposed to biological material who received care at a reference service that was submitted to an intervention based on planned organizational change. Data were collected by using the critical incident technique and analyzed from the perspective of content analysis. Results: twenty exposed workers participated in the study and were split into two groups in the pre- and post-intervention phase. Categories regarding improvement in the guidance they received, reduction in the time they waited once they got to the facility, organization of the process, documentation qualification, and professionalism in carrying out the assistance emerged from the workers' accounts. Conclusions: the present study allowed the exposed workers to visualize the changes that happened in the care management in case of accidents involving biological material. Additionally, there was the recognition of the adopted methodological path, which allowed the active participation of the people involved.